REFORMS AND DEVELOPMENT PROSPECTS IN THE PUBLIC FINANCIAL SYSTEM IN UZBEKISTAN (Journal of Science-Innovative Research in Uzbekistan, 2023)
A large amount of money has been collected in state trust funds under the conditions of the weakening of state financial control, these funds are ineffective use and can lead to various situations. that is why also in order to strengthen control over the use of state financial resources it is appropriate to include them in the state budget. Funds collected in it is necessary to ensure that the target direction remains unchanged. This in the article, the division of the financial system and state budgets into separate areas and sections thoughts and comments are made about it.